Menganalisi Penyebab, Konsekuensi dan Solusi Potret Ketimpangan Ekonomi - Edelweis Bunga Gunung; David Setiawan; Muhammad Yasin (Jurnal Publikasi Ilmu Manajemen, 2023)
This journal aims to analyze the causes, consequences, and solutions related to economic inequality. In an effort to understand the phenomenon of economic inequality, we adopt an analytical approach and collect related statistical data. Through this research, we seek to provide a comprehensive understanding of the problem of economic inequality faced by society. In the analysis of the causes, we identify the factors that contribute to economic inequality. We examine income inequality, unequal access to resources, and unequal economic structure as the main factors influencing economic inequality. By analyzing data and related studies, we seek to understand the role and impact of these factors.